PROSPECTS FOR LEARNING THE RUSSIAN LANGUAGE IN UZBEKISTAN - R. Khojaeva (Modern American Journals, 2025)
This article examines the prospects for the development of Russian language learning in Uzbekistan. It provides a historical overview of how attitudes toward learning Russian have evolved over the centuries. The author explores the emergence of a new multipolar linguistic situation in the country.
Keywords: Russian-speaking population, multiethnic society, bilingualism, language policy, linguistic self-identification, multilingualism, native speaker.